I have a divine call to heal my people: motivations and strategies of Nigerian medicine traders in Guangzhou, China (2020)
This case study explored the motivations and strategies of Nigerian medicine traders in responding to the health-care demands of co-migrants in China using observations and interview data from two Nigerian medicine traders in Guangzhou. The medicine traders initially responded to a ‘divine call’ but they shared similar economic motivations to survive, served predominantly African clientele and relied on ‘flyers’ and family networks to source for medicinal commodities between Nigeria and China. They were similar and different in certain respects and their undocumented statuses affected them in Guangzhou. The case study showed how survival pressures produced African health entrepreneurs in China.